Effect of oral nifedipine on ocular blood flow in patients with low tension glaucoma. Issue 12 (December 1996) - Geyer, O; Neudorfer, M; Kessler, A; Firsteter, E; Lazar, M; Almog, Y
Abstract : AIM: To investigate the effect of oral nifedipine on ocular blood flow in patients with low tension glaucoma (LTG). METHODS: In this prospective study we examined the effects of 3 weeks of treatment with oral nifedipine 30 mg/day in 11 patients with LTG, by using colour Doppler ultrasound imaging to measure haemodynamic variables in the central retinal (CRA), short posterior ciliary (SPCA), and ophthalmic (OA) arteries. Intraocular pressure (IOP) and blood pressures were also evaluated. RESULTS: Nifedipine failed to alter IOP nor did it change peak systolic velocity, end diastolic velocity, or the resistance index in any of the three ocular vessels studied (p > 0.05). However systolic and diastolic systemic arterial blood pressure measurements varied significantly after nifedipine treatment compared with baseline (p < 0.05). CONCLUSION: Our study failed to demonstrate a significant effect of nifedipine on retrobulbar circulation of patients with LTG.